The Impact of Emotional Labor on University Teachers: Theoretical Perspectives and Influencing Factors - Arshad Mahmood Arif,; Tahmina Rashid,; Munir Ahmed Qadri,; Ajaz Sadiq,; Nagarish Zafar, (Dialogue Social Science Review (DSSR), 2024)
This paper investigates the concept of emotional labor among university teachers, emphasizing both the theoretical framework and practical implications in the context of higher education. Emotional labor, which involves regulating emotions to meet organizational expectations, is explored through the lenses of gender, age, qualification, and workload, with a focus on university faculty members. By integrating recent findings and addressing gaps in the literature, this study sheds light on the impact of these factors on the emotional wellbeing of faculty members. The research also provides insights into potential policy reforms for managing emotional labor and improving workplace performance in academic settings.